2021
DOI: 10.1155/2021/9935910
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based MRI in Diagnosis of Fracture of Tibial Plateau Combined with Meniscus Injury

Abstract: This study aimed to explore the application value of magnetic resonance imaging (MRI) images based on deep learning algorithms in the diagnosis of tibial plateau fractures combined with meniscus injuries. The original MRI image was input into the deep learning convolutional neural network (CNN), and the knee joint undersampled and fully sampled MRI image data were used for training to obtain a neural network model that can effectively remove the noise and blur of the undersampled image. Then, the image was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…AI has also been proven to be helpful in detecting soft-tissue injuries around the knee. A study by Xie et al has shown that magnetic resonance imaging scans augmented with AI were able to detect meniscal defects combined with tibial plateau fractures with an accuracy of 95 % and the features were very consistent with intraoperative findings [ 12 ].…”
Section: Introductionmentioning
confidence: 81%
“…AI has also been proven to be helpful in detecting soft-tissue injuries around the knee. A study by Xie et al has shown that magnetic resonance imaging scans augmented with AI were able to detect meniscal defects combined with tibial plateau fractures with an accuracy of 95 % and the features were very consistent with intraoperative findings [ 12 ].…”
Section: Introductionmentioning
confidence: 81%
“…AI has also shown promising results in several other diagnostic applications, ranging from developmental abnormalities to soft-tissue knee injuries. A proof-of-concept investigation by Xie et al (2021) [15] tested a CNN-based algorithm to improve the quality of MRI scans in tibial plateau fractures with combined meniscal defects [16]. The authors documented a sensitivity of 96.9%, specificity of 93.2%, and accuracy of 95.3%, respectively, when MRI diagnostics were compared with arthroscopic findings.…”
Section: Ai and Orthopaedic Surgerymentioning
confidence: 99%
“…AI has also shown promising results in several other diagnostic applications, ranging from developmental abnormalities to soft-tissue knee injuries. A proof-of-concept investigation by Xie et al 42 tested a CNN-based algorithm to improve the quality of MRI scans in tibial plateau fractures with combined meniscal defects. 43 The authors documented a sensitivity of 96.9%, specificity of 93.2%, and accuracy of 95.3%, respectively, when MRI diagnostics were compared with arthroscopic findings.…”
Section: Image Recognition and Diagnosticsmentioning
confidence: 99%
“…This study is one of many that highlights feasible grounds for future research and advancements for current imaging modalities. 42 Regarding congenital abnormalities, such as hip dysplasia, studies have also shown practicalities for radiological measurements in a quick and effective manner. 44 AI-assisted diagnosis and classification of OA from radiographs have demonstrated similar accuracy to senior clinicians.…”
Section: Image Recognition and Diagnosticsmentioning
confidence: 99%